Clinical, Etiological and Laboratory Profile of Children with Disorders of Sexual Development (DSD)-Experience from a Tertiary Pediatric Endocrine Unit in Western India - Jahagirdar, Rahul (Indian J Endocrinol Metab, 2021)
OBJECTIVES: To present the clinical profile, diagnostic work-up, and management of children with Disorders of Sexual Development (DSD). MATERIALS AND METHODS: A retrospective study from a tertiary pediatric endocrine unit of western India. We included 39 patients who presented over a period of 9 years from June 2009 to June 2018. RESULTS: Nineteen patients (48.7%) were diagnosed with 46 XY DSD, 16 (41%) with 46 XX DSD, and 4 (10.3%) with sex chromosomal DSD. Out of 46 XY DSD, androgen insensitivity was observed in 8 (42.1%) patients, 5 alpha-reductase deficiency in 5 (26.3%), gonadal dysgenesis in 3 (15.8%), ovotesticular DSD in 2 (10.5%) and 17 beta-hydroxylase (17γ-HSD3) deficiency in 1 (5.3%). Congenital adrenal hyperplasia was the most common cause in 46 XX DSD observed in 11 (68.75%) out of 16 patients, ovotesticular DSD was seen in 4 (25%) patients and testicular DSD in 1 (6.25%) patient. In sex chromosomal DSD 3 (75%) patients had mixed gonadal dysgenesis and 1 (25%) had ovotesticular DSD out of a total of 4 patients. At presentation gender of rearing was assigned as male in 16 (41%) patients, female in 20 (51.3%) patients, and no gender was assigned in 3 (7.7%). The gender of rearing was changed after diagnosis in 6 (16.7%) children. CONCLUSION: CAH was the most common etiology of 46 XX DSD whereas androgen insensitivity among 46 XY DSD. Assigning the sex of rearing should not be hurried and should be done only after diagnosis and parental counseling. A multidisciplinary and systematic approach is required for children with DSD.